2016
DOI: 10.1136/gutjnl-2015-309784
|View full text |Cite
|
Sign up to set email alerts
|

Activated Schwann cells in pancreatic cancer are linked to analgesia via suppression of spinal astroglia and microglia

Abstract: Objective The impact of glia cells during GI carcinogenesis and in cancer pain is unknown. Here, we demonstrate a novel mechanism how Schwann cells (SCs) become activated in the pancreatic cancer (PCa) microenvironment and influence spinal activity and pain sensation. Design Human SCs were exposed to hypoxia, to pancreatic cancer cells (PCCs) and/or to T-lymphocytes. Both SC and intrapancreatic nerves of patients with PCa with known pain severity were assessed for glial intermediate filament and hypoxia marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
68
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 41 publications
2
68
0
Order By: Relevance
“…S6). This observation is in harmony with our previous findings on the decreasing GFAP content of nerves of PDAC patients with pain (8).…”
Section: Cxcl12/cxcr4/cxcr7 Signaling Mediates Chemoattraction Of Sc Tosupporting
confidence: 93%
See 3 more Smart Citations
“…S6). This observation is in harmony with our previous findings on the decreasing GFAP content of nerves of PDAC patients with pain (8).…”
Section: Cxcl12/cxcr4/cxcr7 Signaling Mediates Chemoattraction Of Sc Tosupporting
confidence: 93%
“…In the present study, we show this chemokine-receptor axis has a role in the activation of peripheral glia, i.e., SC, in the tumor microenvironment, which seems to entail an analgesic effect in the early disease course. Accordingly, we recently demonstrated decreased pain sensation among PDAC patients who bear increased pancreatic gliosis with cellular hypertrophy of pancreatic glia (8). In the light of the previously reported pro-nociceptive roles of CXCR4 and CXCL12, our observations suggest that peripheral and central CXCL12-mediated signaling exert contrasting effects for nociception, i.e., CXCL12 mediating analgesia via modulation of SC activity.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…Schwann cells initiate and mediate neural interactions with cancer cells, particularly in the early stages of pancreatic cancer. In this issue of Gut , Demir et al 4 undertook a comprehensive investigation of Schwann cell involvement in human and mouse pancreatic cancer which revealed that interleukin-6 (IL-6) secreted by activated Schwann cells inhibits pain signalling in the early stages of pancreatic cancer. This novel mechanism has dire implications, as inhibiting pain signalling would delay treatment seeking behaviour and therefore early detection of cancer.…”
mentioning
confidence: 99%